2014
DOI: 10.1038/hdy.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pollen dispersal in a small population of the Canarian endemic palm (Phoenix canariensis)

Abstract: The genetic diversity of small populations is greatly influenced by local dispersal patterns and genetic connectivity among populations, with pollen dispersal being the major component of gene flow in many plants species. Patterns of pollen dispersal, mating system parameters and spatial genetic structure were investigated in a small isolated population of the emblematic palm Phoenix canariensis in Gran Canaria island (Canary Islands). All adult palms present in the study population (n ¼ 182), as well as 616 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…As has been documented for other outcrossing species in small populations (Balloux, 2004;Saro et al, 2014), we observed an excess of heterozygotes in all life stages of C. estrellensis. Owing to the relatively large range of pollen dispersal, one could expect an effective mixing of genes by pollen flow or even seed dispersal within the studied population, hampering SGS.…”
Section: Gene Flowsupporting
confidence: 54%
See 3 more Smart Citations
“…As has been documented for other outcrossing species in small populations (Balloux, 2004;Saro et al, 2014), we observed an excess of heterozygotes in all life stages of C. estrellensis. Owing to the relatively large range of pollen dispersal, one could expect an effective mixing of genes by pollen flow or even seed dispersal within the studied population, hampering SGS.…”
Section: Gene Flowsupporting
confidence: 54%
“…However, immigration rates, most notably for seeds, and mean gene dispersal distances, principally for pollen, were inconsistent between fractional paternity analysis and categorical paternity assignments (Tables 2-5). A discrepancy between paternity approaches has been reported in other mating studies for tree species in small populations (Ottewell et al, 2012;Saro et al, 2014), and this difference likely arises owing to the nature of each analytical approach (Burczyk et al, 2002;Kalinowski et al, 2007).…”
Section: Gene Flowmentioning
confidence: 88%
See 2 more Smart Citations
“…Some years ago, the neighbourhood model was implemented in the NM+ software (Chybicki & Burczyk, ). The software has been successfully applied in a number of studies (e.g., Llorens, Byrne, Yates, Nistelberger, & Coates, ; Sampson, Byrne, Gibson, & Yates, ; Saro, Robledo‐Arnuncio, González‐Pérez, & Sosa, ). However, the fixed structure of the program makes it of limited applicability to specific study designs or questions (e.g., Chybicki & Burczyk, ; Lagache, Klein, Ducousso, & Petit, ).…”
Section: Introductionmentioning
confidence: 99%